Case report: Transcatheter aortic valve replacement in a large bicuspid anatomy using the XL-Myval 32 mm - Elkoumy, Ahmed; Terkelsen, Christian J.; Abdelshafy, Mahmoud; Ellert-Gregersen, Julia; Elzomor, Hesham; Thim, Troels; Serruys, Patrick W.; Soliman, Osama; Nissen, Henrik (Frontiers in Cardiovascular Medicine, 2022)
Transcatheter aortic valve replacement (TAVR) is a recommended intervention for selected population with severe aortic stenosis (AS). Bicuspid aortic valve (BAV) anatomy has been categorized as an unfavorable anatomy for TAVR due to multiple considerations as exclusion from randomized trials in addition to the challenging and unpredictable anatomy. The anatomical constraints of BAV include the large anatomy of the annulus, sinus of Valsalva, and aorta (aortopathy), in addition to significant calcifications of the device landing zone. Most commercial transcatheter heart valves (THV) have upper dimension limits of the annulus and area in which the device can be implanted safely without significant oversizing. Myval-XL THVs (Meril Life Sciences Pvt. Ltd., India) are balloon-expandable valves (BEV) that have been developed with two new sizes, 30.5 and 32 mm, aiming to treat patients with large annulus dimensions and that exceed the upper limit of an ordinary device’s sizing matrix. This case series report describes TAVR using the XL-Myval 32 mm THV in three European patients with symptomatic severe bicuspid aortic stenosis with significant calcifications and large annular dimensions exceeding the limits of the other THVs.